2018
DOI: 10.15406/jmen.2018.06.00186
|View full text |Cite
|
Sign up to set email alerts
|

Influence of periodontal condition on levels of human beta defensins 1 and 2 in saliva

Abstract: Many research studies have looked into periodontal disease biomarkers. The aim of this study was to assess salivary levels of human beta defensin 1 and 2 (hBD-1) and (hBD-2) in different periodontal condition. The Periodontal Screening & Recording (PSR) system, a modification of de Community Periodontal Index Treatment Needs (CPITN), was used to evaluate the periodontal treatment needs of 120 patients without any systemic disease. Salivary levels of hBD-1 and hBD-2 were determined by ELISA. Higher hBD-1 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The quantitative detection of hBDs in oral fluids has been applied in various oral conditions, and the loss of hBD is not routinely encountered [41,[50][51][52][53][54][55]. Studies have shown that individuals with periodontitis could have higher levels of hBDs in their saliva compared to individuals without periodontitis [52][53][54]56,57]. Additionally, research has also shown that there is a positive correlation between the severity of periodontitis in diabetic individuals and hBD levels, meaning that as the severity of periodontitis increases, so do hBD levels [56,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative detection of hBDs in oral fluids has been applied in various oral conditions, and the loss of hBD is not routinely encountered [41,[50][51][52][53][54][55]. Studies have shown that individuals with periodontitis could have higher levels of hBDs in their saliva compared to individuals without periodontitis [52][53][54]56,57]. Additionally, research has also shown that there is a positive correlation between the severity of periodontitis in diabetic individuals and hBD levels, meaning that as the severity of periodontitis increases, so do hBD levels [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that individuals with periodontitis could have higher levels of hBDs in their saliva compared to individuals without periodontitis [52][53][54]56,57]. Additionally, research has also shown that there is a positive correlation between the severity of periodontitis in diabetic individuals and hBD levels, meaning that as the severity of periodontitis increases, so do hBD levels [56,57]. Pereira et al found that patients with periodontitis displayed elevated levels of HBD-2 and hBD-3 in their oral fluids compared to healthy individuals [52,53].…”
Section: Discussionmentioning
confidence: 99%